(untitled) (Bangladesh Journal of Medical Microbiology, 2012)
Accreditation of health laboratories is the process by which an independent and authorized agency accredits the quality system and competence of a laboratory on the basis of certain pre-defined standards. Accreditation is done at regular intervals to ensure maintenance of standards and reliability of results generated to support clinical and public health activities by the laboratories. DOI: http://dx.doi.org/10.3329/bjmm.v6i1.19363 Bangladesh J Med Microbiol 2012; 06(01): 22-28